Sharpening the Axe: Identifying and Closing Gaps Within the Training Space of the South African Private Security Industry - Mbana, Linda; Mofokeng, Jacob T.; Maluleke, Witness; Khosa, Dorcas (International Journal of Criminology and Sociology, 2021)
The ever-present threat of crime in South Africa continues to drive the rise and demand for Private Security Industry (PSI) services amongst various governmental institutions, businesses and citizens to ensure their safety. This rise for the Private Security Services (PSS) persistently presents new challenges to the Private Security Industry Regulatory Authority (PSiRA) such as poor security training standards and deployment of untrained security officers attached to the Private Security Companies (PSCs), which negatively impacts the professionalism of the security industry. This study was guided by this objective: Identifying and closing the gaps within South African training space of PSI. This qualitative study was guided by the exploratory research design. The judgemental sampling technique was adopted to sample 40 participants confined to Gauteng (GP), Kwa-Zulu Natal (KZN) and Western Cape (WC) Provinces. The selected relevant stakeholders were attached to the South African Police Service (SAPS), Department of Labour (DoLl), Department of Home Affairs (DoH), National Prosecuting Authority (NPA) and the legal fraternity) and the PSI Directors and security officers to form part of the Focus Group Discussions (FGDs) and hybrid semi-structured interviews. The findings highlighted that the majority of the participants agreed that the private security industry training space is affected by security service providers letting PSiRA down by not training at, but rather engaging in, criminal activity through selling and people buying PSiRA security certificates. Some of the challenges mentioned include; poor training standards, non-compliance to legislated training standards, unqualified security training facilitators and outdated security Grades, misuse of security equipment leading to serious injuries and death, corruption in the industry, some of it being perpetrated by PSiRA inspectors, the very people who are supposed to keep the industry in check. This study recommends that, in order to overcome the challenges in the security training space, PSiRA needs to do away with the outdated security Grades by developing a new policy framework which will enable the creation of a new security-training curriculum and revise the training methods to suit the ever-changing security industry.